Ethnic Relations Syllabus at the University of Malaya - Mohd Hussain, Rosila Bee (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2011)
Due to the various justification within the issues of ethnic relations in Malaysia, few ideas and factors are still misled. In order to provide a clearer picture of the scenario, a particular set of syllabus had been laid out for the respective students of University Malaya. The syllabi is an additional effort put forward in supporting the ongoing efforts by governments and various parties to uphold the national unity. Among the topics that wil be concentrated on will essentially be on the introduction of the various ethnic groups in Malaysia including from Sabah and Sarawak, the background (theoretical) of various ethnic groups including the economic factors, social-cultural factors and political factors. Once the caption is clear, they will be introduced to the various terms and situations that came mutually in the process of ethnic relations, such as the idea of assimilation, acculturation, polarization, segregation, prejudice etc. Finally, with all given information, the idea will be applied and further discussed based on the previous and current scenario, experiences and circumstances of how Malaysia can uphold and maintain its ethnic relations and national unity.